Permittivity of biodiesel-rich blends with fossil diesel fuel: Application to biodiesel content estimation - Corach, Julián (2016)
The relative permittivity of biodiesel-rich blends, from pure biodiesel to 50% blends with diesel fossil fuel, were determined at temperatures between 303.0 K and 343.0 K (controlled within ±0.1 K). Measurements were made on biodiesel from soybean in the frequency range from 20 kHz to 2 MHz; the relative measurement uncertainty was below 0.3%. At each composition, experimental values fit very satisfactorily to a linear dependence on temperature. Similarly, at constant temperature, permittivity depends linearly on biodiesel content. From these results, a simple model was proposed to estimate the permittivity of the samples as a function of biodiesel content and temperature. The model parameters were determined from a multiple regression analysis. The RMS uncertainty of the fitting was below 0.7%, for blends with biodiesel concentration ≥50%. The model was inverted to determine the biodiesel content from permittivity and temperature measurements. The parameters of the inverted model were checked by a multiple regression analysis and the RMS uncertainty of the content determination was below 1.5%. The results presented in this work show that dielectric measurements are a valuable tool for biodiesel content determination in rich-biodiesel blends from vegetable oils with diesel fossil fuel.